On the value of surface saturated area dynamics mapped with thermal infrared imagery for modeling the hillslope‐riparian‐stream continuum. Issue 10 (28th October 2016) - Glaser, Barbara; Klaus, Julian; Frei, Sven; Frentress, Jay; Pfister, Laurent; Hopp, Luisa
Abstract: The highly dynamic processes within a hillslope‐riparian‐stream (HRS) continuum are known to affect streamflow generation, but are yet not fully understood. Within this study, we simulated a headwater HRS continuum in western Luxembourg with an integrated hydrologic surface subsurface model (HydroGeoSphere). The model was setup with thorough consideration of catchment‐specific attributes and we performed a multicriteria model evaluation (4 years) with special focus on the temporally varying spatial patterns of surface saturation. We used a portable thermal infrared (TIR) camera to map surface saturation with a high spatial resolution and collected 20 panoramic snapshots of the riparian zone (approx. 10 m × 20 m) under different hydrologic conditions. Qualitative and quantitative comparison of the processed TIR panoramas and the corresponding model output panoramas revealed a good agreement between spatiotemporal dynamic model and field surface saturation patterns. A double logarithmic linear relationship between surface saturation extent and discharge was similar for modeled and observed data. This provided confidence in the capability of an integrated hydrologic surface subsurface model to represent temporal and spatial water flux dynamics at small (HRS continuum) scales. However, model scenarios with different parameterizations of the riparian zone showed that discharge and surface saturation were controlled by different parameters and hardly influenced each other. Surface saturation only affected very fast runoff responses with a small volumetric contribution to stream discharge, indicating that the dynamic surface saturation in the riparian zone does not necessarily imply a major control on runoff generation. Key Points: We validate modeled dynamic surface saturation patterns with ground‐based thermal infrared images We verify the performance of an integrated hydrologic model on small scales (centimeters to meters) Discharge and surface saturation are related but controlled by different parameters